Theoretical Study on Heating Process of Micro-Al Particles in Laminar Flame. Issue 5 (4th April 2023) - Gu, Xingpeng; Li, Junwei; Han, Lei; Wang, Yangbin; Wang, Ningfei
ABSTRACT: In order to understand heating process of micro-aluminum particles in hot gas environment, preheating model and oxide film rupture models are established to analyze heating and rupture of oxide film procedure before Al particle combustion. Studying heating process of Al particles can better understand the heating phenomenon, including rupture and agglomeration of Al particles during heating. In oxide film rupture model, a thermal-stress-rupture (TSR) model is established for Al core in solid state, which describes extruding stress between oxide film and aluminum core due to different expansion coefficients. A molten-aluminum-state (MAS) model is established after Al core melts, which describes the relationship between pressure of liquid Al core and heating temperature. Results indicate that as diameter of Al particles increases, preheating time becomes longer. Rupture temperature of the oxide film is higher than the melting point of Al. It is better to use the rupture temperature to calculate preheating time. Additionally, the proposed heating model can predict preheating time of micro-Al particles more accurately than Sundaram's model. For particle with diameter of 68.3/84/121.6 μm in Feng's experiments, prediction deviation of this study is only 27.6%/3.8%/4.3%, respectively.